Pengaruh Net Profit Margin (NPM) Dan Return on Equity (ROE) Terhadap Harga Saham: Studi Pada Perusahaan Sub Sektor Food and Beverage Di Bursa Efek Indonesia (BEI) Periode Tahun 2012-2015 - Ani Sumarni; Bulan Tati Fitria; Indri Ayu Tansar; Soelaeman Sukmalana (Majalah Bisnis & IPTEK, 2022)
The share price is the share value that reflects the company's wealth that issued the shares. So that the greater the value of the stock price, the higher the value of the company. This study aims to prove the effect of Net Profit Margin (NPM) and Return on Equity (ROE) on stock prices. The research method used in this study is a descriptive verification method on Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2012-2015 period. To obtain data and information that will support this research, namely by collecting secondary data and testing the multiple regression hypothesis to determine the effect of NPM and ROE on stock prices. Based on the study results showing the results of multiple regression, the equation Y=-144618,665+5167,671 X+6846,367 X from the t-test results obtained t-count results of 2,242 with a significant level of 0.05, which is greater than the t-table value of 2.042. From the value R square, it knows that the influence of NPM and ROE Financial Ratios affects stock prices by 0.695 or 69.5%, while the rest is the influence of other factors (variables) not examined. Therefore, the research results above can conclude that NPM and ROE significantly influence stock prices. The research implication suggested increasing the Net Profit Margin (NPM) and Return on Equity (ROE) of the company's stock price in the food and beverage sub-sector on the Indonesia Stock Exchange. To the company if the management performance is good.